2002
DOI: 10.3354/meps234001
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual changes in the biodiversity and community structure of the macrobenthos in Tees Bay and the Tees estuary, UK, associated with local and regional environmental events

Abstract: Abundances of macrobenthic species were monitored twice yearly (March and September) at 6 locations in Tees Bay, UK, between 1973 and, and once yearly at 4 stations in the outer Tees estuary and 7 stations in the inner estuary between 1980 and 1999. In the Bay, multivariate analysis revealed a serial pattern of community change over years for all areas, but with a major shift in community composition between 1986 and 1988. Inter-annual variability in community composition was significantly greater after 1987 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 24 publications
(20 reference statements)
7
66
0
7
Order By: Relevance
“…From a general biodiversity management point of view, sustaining high + is considered as desirable, and low + indicates ecosystem degradation due to human disturbances. This has been confirmed by a number of studies based on different taxa (e.g., nematodes, molluscks, polychaeta, insects, fishes) (Jiang et al, 2014;Leonard et al, 2006;Marchant, 2007;Milosevic et al, 2012;Warwick et al, 2002). However, our study shows that the pristine fish fauna of an isolated Lake had a relatively low + , and the + increased with growing anthropogenic disturbances such as exotic species introductions and native species extirpation.…”
Section: Discussionsupporting
confidence: 33%
“…From a general biodiversity management point of view, sustaining high + is considered as desirable, and low + indicates ecosystem degradation due to human disturbances. This has been confirmed by a number of studies based on different taxa (e.g., nematodes, molluscks, polychaeta, insects, fishes) (Jiang et al, 2014;Leonard et al, 2006;Marchant, 2007;Milosevic et al, 2012;Warwick et al, 2002). However, our study shows that the pristine fish fauna of an isolated Lake had a relatively low + , and the + increased with growing anthropogenic disturbances such as exotic species introductions and native species extirpation.…”
Section: Discussionsupporting
confidence: 33%
“…Even when longterm observational data is available, the timing of changes in different-ecosystem response variables may be lagged, confusing early-warning signals. Long-term studies of the benthic communities off the NE coast of England have shown increased interannual variability and decreased multi-variate stability (Warwick et al 2002), but only after abrupt changes in the water column associated with a regime shift (Reid et al 2001).…”
Section: Indicators Of Regime Shifts and Changes To Resilience In Ecomentioning
confidence: 99%
“…The North Sea regime shift has involved an increase in phytoplankton biomass, and changes in plankton community structure, diversity and phenology (Reid et al 1998;Beaugrand 2004). The shift was detected in both pelagic and benthic realms (Kröncke et al 1998;Reid and Edwards 2001;Warwick et al 2002). Parallel changes occurred in large-scale and regional temperatures, in three trophic levels and in both holozooplanktonic and merozooplanktonic components (Kirby and Beaugrand 2009).…”
Section: Regime Shift In the North Sea Plankton Communitymentioning
confidence: 99%